Biology and courting behaviour of Neurothemis tullia (Drury) (Odonata: Libellulidae) - Norwahidah Saibani (2005., 2005)
Neurothemis tulia is a dragonfly belonging to the family Libellulidae and order Odonata.Drangonfly are generally predators in rice-fields hence can act as a biological control agent in roce pests.The objective of this module is to produce an interesting anfd effective teaching and learning module through multimedia application. In this module,some of the biological aspects and behaviour of this dragonfly are desingned in an interactive way.3D animation is used in order to showthe courting behaviour.In addition to that module is desingned based on the storyboard and incorporation of softwares including Authorware 6.0,Adobe Photoshop 7.0,3D Studio Max 6.0 and Sonic Foundry Sound Forge 6.0.Users can learn in an interactive manner the biology and couting behaviour of Neurothemis tullia from the multimedia product.
Project paper (B.S.Cum.Ed.(Hons.)) - Universiti Putra Malaysia, 2005.